Surplus approach, Historical Materialism, and precapitalist economies: Some open questions - Sergio Cesaratto (PSL Quarterly Review)
In the classical economists’ surplus approach retrieved by Sraffa (1951; 1960) and Garegnani ([1960] 2024), institutions regulate the material basis of society and, in particular, the extraction and distribution of the social surplus. In this regard, classical theory provides a material anchor, alternative to neoclassical New Institutional Economics, to anthropological, archaeological and historical studies of precapitalist economies. Expunged of any teleological meaning, Marx’s Historical Materialism (HM) is a natural source of inspiration for this interdisciplinary perspective. The nature and dynamics of Marx’s notion of modes of production (MOP) are not, however, firmly defined and have been the object of over-complicated doctrinal disputes among Marxists. Since I am unable to provide a comprehensive overview of these debates, I will limit myself to a few aspects that seem to me to be most central or that best convey the issue. The question of MOP dynamics is the most relevant and complex. All in all, the most mature Marx leaves us a very flexible reading of HM as a method of connecting economic, social, and institutional history that can be broadly shared by non-Marxists.